When and how much does new transport infrastructure add to property values? Evidence from the bus rapid transit system in Sydney, Australia. (October 2016) - Mulley, Corinne; Tsai, Chi-Hong (Patrick)
Abstract: This paper examines the timing of the impact of a Bus Rapid Transit (BRT) system on residential housing prices in Sydney, Australia. A multilevel model is employed to identify the housing price uplift after the opening of the BRT system. Catchment and control areas are selected from the property sales data to control for the potential external shocks to house prices. The modelling takes account of the property, neighbourhood and accessibility attributes which are expected to affect the property transaction price to quantify the land value uplift from the BRT system and the point in time when it occurs. This research found that the sales price of residential properties within 400 m of BRT stops are marginally higher than those outside of the BRT service area after the opening of the BRT system in 2003 and 2004. The research outcomes provide evidence to government sectors for planning future BRT systems and for quantifying the potential to raise financial funding for public transport improvement through the gain of land value uplift. Highlights: Land value uplift from a new bus rapid transit system in Sydney is explored. Timing of uplift explored in announcement, building and operational phases. Weak support for positive value uplift from bus rapid transit after operation. Multilevel modelling used to explore the timing of uplift. Comparison with other BRT concludes lower uplift in Sydney.